2015
DOI: 10.3390/molecules20011118
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Content and Antioxidant Capacity in Algal Food Products

Abstract: Abstract:The study objective was to investigate total phenolic content using Folin-Ciocalteu's method, to assess nine phenols by HPLC, to determine antioxidant capacity of the water soluble compounds (ACW) by a photochemiluminescence method, and to calculate the correlation coefficients in commercial algal food products from brown (Laminaria japonica, Eisenia bicyclis, Hizikia fusiformis, Undaria pinnatifida) and red (Porphyra tenera, Palmaria palmata) seaweed, green freshwater algae (Chlorella pyrenoidosa), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
227
8
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 339 publications
(256 citation statements)
references
References 41 publications
10
227
8
11
Order By: Relevance
“…Cyanobacteria could be one of the most potential source for the production of natural antioxidants. Phenolic acids and flavonoids from plant sources have been well-documented for their antioxidant, free-radical quenching and redox metal ion-chelating affects (Singh et al 2009(Singh et al , 2014Tutour 1990;Apati et al 2003;Hossain et al 2016) but cyanobacteria and microalgae are relatively new source for such compounds in recent years due to their potential benefits and ease of production (Guedes et al 2013;Machu et al 2015). Gallic, chlorogenic, caffeic and ferulic acids identified from plant sources have been known as strong antioxidants and free radical scavengers (Piazzon et al 2012;Babić et al 2015) but their presence in cyanobacteria is scarcely reported and this make these organisms more potential.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyanobacteria could be one of the most potential source for the production of natural antioxidants. Phenolic acids and flavonoids from plant sources have been well-documented for their antioxidant, free-radical quenching and redox metal ion-chelating affects (Singh et al 2009(Singh et al , 2014Tutour 1990;Apati et al 2003;Hossain et al 2016) but cyanobacteria and microalgae are relatively new source for such compounds in recent years due to their potential benefits and ease of production (Guedes et al 2013;Machu et al 2015). Gallic, chlorogenic, caffeic and ferulic acids identified from plant sources have been known as strong antioxidants and free radical scavengers (Piazzon et al 2012;Babić et al 2015) but their presence in cyanobacteria is scarcely reported and this make these organisms more potential.…”
Section: Resultsmentioning
confidence: 99%
“…Total phenolic content (TPC) in the cyanobacterial strains was assessed using Folin-Ciocalteu's reagent (Machu et al 2015). Gallic acid was used as standard compound and total phenol content was expressed in terms of mg gallic acid equivalents (GAE) g -1 fresh wt.…”
Section: Estimation Of Total Phenolics and Flavonoidsmentioning
confidence: 99%
“…Senyawa fenolik pada alga cokelat memiliki komponen struktural yang tidak terpisahkan dari dinding sel dan memiliki berbagai fungsi perlindungan dari radiasi UV, berperan dalam reproduksi alga dan mekanisme perlindungan terhadap faktor biotik serta memiliki sifat terapeutik (Machu et al 2015). Senyawa bioaktif yang memiliki peranan sebagai antioksidan, mampu menghambat dihasilkannya agen oksidatif dalam produksi Reactive Oxygen Spesies (ROS) oleh sel darah perifer, menghambat paparan oksidatif dalam tubuh dan berperan dalam proses penurunan tekanan darah (Septian dan Widyaningsih 2014).…”
Section: Pendahuluanunclassified
“…Perbedaan total fenolik pada rumput laut disebabkan oleh beberapa faktor seperti jenis alga, geografis, musim, fisiologis dan keadaan lingkungan yang bervariasi (Machu et al 2015).…”
Section: Kadar Total Fenolikunclassified
“…Most of the time, the levels of free radicals in living organisms are controlled by a complex set of antioxidant defences, which minimize oxidative damage to important bio molecules, but under oxidative stress, endogenous antioxidants are not enough to deal with the increased levels of ROS 15,16 . This free radical, stable at room temperature, is reduced in the presence of an antioxidant molecule, giving rise to colourless ethanol solution.…”
Section: Introductionmentioning
confidence: 99%